Informing CSA implementation at national, regional, and continental scales - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
CCAFS Scientists at the World Agroforestry Centre (ICRAF), the International Center for Tropical Agriculture(CIAT), the International Maize and Wheat Improvement Center (CIMMYT), and the International Livestock Research Institute (ILRI) are developing two “Practical Guides” (PGs) on Climate-‐ Smart Agriculture (CSA), partnering with African governments and Universities, the New Economic Partnership for African Development (NEPAD), UN Food Agriculture Organisation (FAO), the Common Market for Eastern and Southern Africa (COMESA), and civil society organisations. The first PG has already been cited by the Kenyan CSA Country Program, which has informed Kenya’s Intended Nationally Determined Contributions (INDC) to the United Nations Framework Convention on Climate Change (UNFCCC). PG1 is focused on disseminating conservation agriculture techniques. Although the second PG is still a work in progress, it will likely influence the plans of at least five national governments, three Regional Economic Communities, and five inernational Nongovernmental Organisations (iNGOs). PG2 will develop based on stakeholder feedback received from PG1, with a new “farming component-‐based” approach. The funding landscape for CSA is rapidly developing, meaning that both Practical Guides have the potential to influence millions of dollars of investments in the near future.